Povezanost med ravnijo izvirnosti likovnega izraza učencev pri pouku likovne umetnosti in ravnijo njihove strpnosti do raznolikosti - Huzjak, Miroslav (Revija za elementarno izobraževanje, 2017)
The aim of this research was to examine the connection between the originality level in children's expression during visual art lessons and their level of tolerance for difference. The participants comprised primary school pupils from grades one, two and three, a total of 110. It was confirmed that there was a statistically significant difference between the pupils who had an introduction to the lesson using the didactic model of visual problem-based teaching and those who had not. Learning and setting art terminology, the analysis of motifs and explanation, as well as demonstration of art techniques resulted in a higher level of creativity in visual performance, as well as a higher level of tolerance. It can be concluded that, with the proper choice of didactic models in teaching the visual arts, a wide range of pupil attitudes and beliefs can be improved.
Keywords: likovna vzgoja; visual art; visual arts; didactics; likovna umetnost; metodika; originality; strereotype; učne metode; children's drawing; izvirnost; stereotipi; otroško risanje; začetni pouk; osnovne šole